Mathematical equation correction to spectral and transport interferences in high-resolution continuum source flame atomic absorption spectrometry: determination of lead in phosphoric acid - Raposo Jr, Jorge Luiz [UNESP]; Oliveira, Silvana Ruella de [UNESP]; Nóbrega, Joaquim Araújo; Gomes Neto, José Anchieta [UNESP] (Editora Unesp, 2010)
Um método de correção de interferência espectral e de transporte é proposto, e foi aplicado para minimizar interferências por moléculas de PO produzidas em chama ar-acetileno e de transporte causada pela variação da concentração de ácido fosfórico. Átomos de Pb e moléculas de PO absorvem a 217,0005 nm, então Atotal217,0005 nm = A Pb217,0005 nm + A PO217,0005 nm. Monitorando o comprimento de onda alternativo de PO em 217,0458 nm, é possível calcular a contribuição relativa de PO na absorbância total a 217,0005 nm: A Pb217,0005 nm = Atotal217,0005 nm - A PO217,0005 nm = Atotal217,0005 nm - k (A PO217,0458 nm). O fator de correção k é a razão entre os coeficientes angulares de duas curvas analíticas para P obtidas a 217,0005 e 217,0458 nm (k = b217,0005 nm/b217,0458 nm). Fixando-se a taxa de aspiração da amostra em 5,0 ml min-1, e integrando-se a absorbância no comprimento de onda a 3 pixels, curvas analíticas para Pb (0,1 - 1,0 mg L-1) foram obtidas com coeficientes de correlação típicos > 0,9990. As correlações lineares entre absorbância e concentração de P nos comprimentos de onda 217,0005 e 217,0458 foram > 0,998. O limite de detecção de Pb foi 10 µg L-1. O método de correção proposto forneceu desvios padrão relativos (n=12) de 2,0 a 6,0%, ligeiramente menores que os obtidos sem correção (1,4-4,3%). As recuperações de Pb adicionado às amostras de ácido fosfórico variaram de 97,5 a 100% (com correção pelo método proposto) e de 105 a 230% (sem correção).

In this work, a new mathematical equation correction approach for overcoming spectral and transport interferences was proposed. The proposal was applied to eliminate spectral interference caused by PO molecules at the 217.0005 nm Pb line, and the transport interference caused by variations in phosphoric acid concentrations. Correction may be necessary at 217.0005 nm to account for the contribution of PO, since Atotal217.0005 nm = A Pb217.0005 nm + A PO217.0005 nm. This may be easily done by measuring other PO wavelengths (e.g. 217.0458 nm) and calculating the relative contribution of PO absorbance (A PO) to the total absorbance (Atotal) at 217.0005 nm: A Pb217.0005 nm = Atotal217.0005 nm - A PO217.0005 nm = Atotal217.0005 nm - k (A PO217.0458 nm). The correction factor k is calculated from slopes of calibration curves built up for phosphorous (P) standard solutions measured at 217.0005 and 217.0458 nm, i.e. k = (slope217.0005 nm/slope217.0458 nm). For wavelength integrated absorbance of 3 pixels, sample aspiration rate of 5.0 ml min-1, analytical curves in the 0.1 - 1.0 mg L-1 Pb range with linearity better than 0.9990 were consistently obtained. Calibration curves for P at 217.0005 and 217.0458 nm with linearity better than 0.998 were obtained. Relative standard deviations (RSD) of measurements (n = 12) in the range of 1.4 - 4.3% and 2.0 - 6.0% without and with mathematical equation correction approach were obtained respectively. The limit of detection calculated to analytical line at 217.0005 nm was 10 µg L-1 Pb. Recoveries for Pb spikes were in the 97.5 - 100% and 105 - 230% intervals with and without mathematical equation correction approach, respectively.
Keywords: método de correção por equação matemática; espectrometria de absorção atômica com fonte contínua e de alta resolução; chumbo; ácido fosfórico; mathematical equation correction approach; high-resolution continuum source flame atomic spectrometry; lead, phosphoric acid